Medicaid insurance in old age - Mariacristina De Nardi; Eric French; John Bailey Jones (Federal Reserve Bank of Chicago, 2012)
Medicaid was primarily designed to protect and insure the poor against medical shocks. Yet, poorer people tend to live shorter lifespans and incur lower medical expenses before death than richer people. Taking these and other important dimensions of heterogeneity into account, and carefully modeling key institutional aspects, we estimate a structural model of savings and endogenous medical expenses to assess the costs and benefits of Medicaid for single retirees. We show that even higher-income retirees benefit from Medicaid, if they live long enough for their resources to be depleted by medical expenses. We also find that all retirees value Medicaid insurance coverage highly, compared to the value of the Medicaid transfers that they actually receive on average.
Keywords: 330